Strategi Pengelolaan Sampah Pada Tempat Pemrosesan Akhir (TPA) Buantan Besar di Kecamatan Siak Kabupaten Siak Provinsi Riau - Rony Setyawan; Aras Mulyadi; Rahman Karnila (Pelantar Press, 2023)
Trash problem nowadays becomes one of global problems, in line with the increase number of population it will not be apart from the increase volume of trash, meanwhile the landfills (TPA) is getting decrease of its capacity. The similar problem was experienced by Siak Regency especially at TPA Buantan Besar. The problem occurred was the trash management was not in line with the technique of management and method that has environmental insight until it causes negative impact on the environment. This research aimed to analyze the characteristics and behavior of the community living around TPA Buantan Besar and to formulate the trash management strategy. The research was conducted in March-July 2020. The measurement result in the field on domestic trash composition at TPA Buantan Besar shows that plastic trash (unorganic) is the most trash found (37,94%), next is the component percentage of food trash category (27,26%), leaf/crop residues trash (8,42%), and paper (6,49%). The community who lives around TPA Buantan Besar has good knowledge and behavior on trash management. The improvements of Buantan Besar Landfills management strategy are optimizing the commitment of Siak Regency Government on trash management through Green Siak Policy, Optimizing Local Regulation related to Trash Management through the support of Local Head of Siak Regency and optimizing the budget of trash management in Siak Regency, optimizing the commitment of Siak Regency Government in decreasing the improvement volum of trash, and institution reinforcement of trash mangement in the region and improving trash service to decrease the conflict arounds the landfills